PENGARUH BAHAN PENGEKSTRAK DAN TINGKAT KADAR AIR TERHADAP VIABILITAS DAN VIGOR BENIH KAKAO (Theobroma cacao L.) - Suldahna Suldahna; Hasanuddin Hasanuddin; Erida Nurahmi (Universitas Teuku Umar, 2018)
This research is intended to determine the effect of extracting materials and appropriate levels of water content on cocoa seeds, and whether or not there are any differences between the viability and the vigor of cocoa beans. The research was conducted at the Laboratory of Seed Science and Technology of the Faculty of Agriculture of Syiah Kuala University. The experimental design used was Completely Randomized Design of 3 x 3 factorial pattern with 3 x replications, so there were 9 treatment combinations and 27 experimental units. The factors studied were extracts consisting of 3 levels, namely: husk ash, sawdust and whiting and three levels of air three levels, namely: 30%, 25%, and 15%. Measurable benchmarks include Growing Potential (PT), Growing Power (DB), Vigor Index (IV), Growth Rate (KCT), Growth Unity (KST), Time Required to Achieve 50% of Total Relative Germination (T50) and Normal Dry Sprout Weight (BKKN). The results of this study showed that extracting foods are very strong on the viability and strength of the cocoa seeds, which is balanced by the growth potential benchmarks (PT), power growth (DB), growth rate (KCT), growing lavency (KST), the time required to achieve 50% germination total (T50), vigor index (IV) and normal germination weight (BKKN). Meanwhile, fertility rate grew (KST), time needed to reach 50% total relative germination (T50), spirit index (IV) and normal dried germination (BKKN). The results of this study can be concluded that there is a very real interaction between the treatment of extracting materials with cocoa beans content levels. The interaction between sawdust and 30% moisture content is the best combination. Reproduction extracting materials to the effectiveness of increasing viability and vigor of cocoa seeds. The best extraction material is found in the sawdust extracting material. The degree of air hardness to the strength of increased viability and strength of cocoa seed. The best levels of cocoa seed air are found at 30%. Keywords: cocoa, extract, seed